Common Hazards to Consider during Manufacturing of Feeds for Swine: AN357, 9/2019 - Langford, Taylor; McKinney, Morgan; Carr, Chad; Scheffler, Jason M (EDIS, 2019)
This 8-page document discusses common biological, chemical, and physical hazards that may need preventive measures during the manufacture of swine feeds. Written by Taylor Langford, Morgan McKinney, Chad Carr, and Jason M. Scheffler, and published by the UF/IFAS Department of Animal Sciences, September 2019. https://edis.ifas.ufl.edu/an357